Factors Influencing Online Game Addiction and Online Game Satisfaction and Loyalty - Xu, Wen (2014)
Purpose – The paper’s aim is to explore the factors that affect the online game addiction and the role that online game addiction plays in the relationship between online satisfaction and loyalty. Methodology – A survey of online game players was conducted, with 300 valid responses collected. Structure equation modelling – specifically partial least squares – was used to assess the relationships in the proposed research framework. Findings – The results indicate that perceived playfulness and descriptive norms influence online game addiction. Furthermore, descriptive norms indirectly affect online game addiction through perceived playfulness. Addiction also directly contributes to loyalty and attenuates the relationship between satisfaction and loyalty. This finding partially explains why people remain loyal to an online game despite being dissatisfied. Practical implications – Online gaming vendors should strive to create amusing game content and to maintain their online game communities in order to enhance player’s perceptions of playfulness and the effects of social influences. Also, because satisfaction is the most significant indicator of loyalty, vendors can enhance loyalty by providing better services, such as fraud prevention and the detection of cheating behaviors. Value – The value of this study is that it reveals the moderating influences of addiction on the satisfaction-loyalty relationship and factors that contribute to the online game addiction. Moreover, while many past studies focused on addiction’s negative effects and on groups considered particularly vulnerable to Internet addiction, this paper extends previous work by investigating the relationship of addiction to other marketing variables and by using a more general population, mostly young adults, as research subjects.